Wady wrodzoneThe analysis of outcomes in 2542 procedures performed in one supraregional referral congenital heart surgical centre between 2001 and 2005 - Kansy, Andrzej; Maruszewski, Bohdan; Burczyński, Piotr; Pastuszko, Andrzej; Birbach, Mariusz; Lipiński, Wojciech; Mirkowicz-Małek, Małgorzata; Mozol, Krzysztof; Kozłowski, Michał; Manowska, Małgorzata; Tobota, Zdzisław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Aim: The aim of this study was the analysis of early outcomes of the congenital heart procedures performed in 100% of children with congenital heart disease between 2001 and 2005. Material and methods: All surgical data underwent analysis according to International Nomenclature for Congenital Heart Disease of the EACTS/STS. The international Aristotle Score method was applied to evaluate the complexity and surgical performance (Basic Score). Patients were divided by age into: all, infants (excl. neonates) and neonates. Procedures were divided into CPB and non-CPB groups and into simple and complex. The outcomes underwent evaluation in the whole material and by years. Results: Out of 2542 procedures 1210 (47.6%) were performed under 1 year of age, including 394 neonates. There were 1656 (65.1%) CPB and 886 (34.9%) non-CPB procedures. 67.7% of CPB procedures performed are defined as “simple” and 32.3% as “complex”. Mean Aristotle Basic Score was 6.17 (95% CI 6.1-6.3). Median age of all patients who underwent 2542 CHS procedures was 13.8 months, 20.1-11.2, p<0.0002. Overall early mortality was 3.9% (5.1-2.8%). CPB procedures carried 4.5% mortality (5.26-3.85%). “Simple” CPB procedures – 0.6%. Mortality in non-CPB procedures was 2.7% (4.8-0.6%). The mortalities in age groups were as follows: all – 3.9%, infants 3.8%, neonates 13.7%. Post-operative median IPPV time was 9 hours in all patients, 82.5 in neonates and 16 in infants. Conclusions: The continuous analysis of outcomes in day-to-day surgical practice has become the duty of the modern congenital heart surgeon.